Development of a Project-Based Learning Model Assisted by the Interactive Canva Application to Improve Creative Thinking and Collaboration Skills of Fourth Grade Elementary School Students - Kartini, Yanti Aprianti; Hendriana, Heris; Septiyan Rahayu, Galih Dani (Program Magister Teknologi Pendidikan Universitas Jambi, 2026)
This study aims to develop a Project-Based Learning (PjBL) model assisted by the interactive Canva application to improve the creative thinking skills and collaboration skills of fourth-grade elementary school students. This study uses the Research and Development (R&D) method with reference to the Borg & Gall development model. The research stages consist of a preliminary study stage, a limited trial, a main field trial, and an operational field trial. The research subjects involved 140 fourth-grade elementary school students in Purwakarta Regency. The instruments used were interview guidelines, observation sheets, questionnaires, and creative thinking ability tests. Data analysis was carried out qualitatively and quantitatively with the help of SPSS software. The Wilcoxon non-parametric test was applied because the data distribution was not normal. The results of the study indicate that the developed learning model is declared very valid based on expert assessment. The trial results show that the PjBL model assisted by interactive Canva received positive to very positive responses from students. In addition, the effectiveness of the learning model is demonstrated by the increase in students' creative thinking skills with N-gain values in the high category. Students' collaboration skills also increased and are in the effective category. Thus, the PjBL model assisted by the interactive Canva application is feasible and effective for use in learning to improve the creative thinking skills and collaboration skills of fourth grade elementary school students.